Antibacterial Activity of MTA Fillapex and AH 26 Root Canal Sealers at Different Time Intervals - Jafari, Farnaz; Samadi Kafil, Hossein; Jafari, Sanaz; Aghazadeh, Mohammad; Momeni, Tahereh (Iranian Endodontic Journal, 2016)
Introduction: The main goal of endodontic treatment is elimination of bacteria and their by-products from infected root canals. This study compared the antibacterial effect of two different sealers, AH 26 and MTA Fillapex, on 4 microorganisms 24, 48 and 72 h and 7 days after mixing. Methods and Materials: The microorganisms used in this study consisted of Lactobacillus acidophilus (ATCC 4356), Lactobacillus casei (ATCC 39392), Staphylococcus aureus (ATCC 25923) and Enterococcus faecalis (ATCC 29212). This test is based on the growth of bacteria and turbidity measurement technique using a spectrophotometer, and direct contact was conducted. Multiple comparisons were carried out using repeated-measures ANOVA followed by Tukey’s test and student’s t-test. The level of significance was set at 0.05. Results: The antibacterial activity in the indirect technique was more than the technique with both sealers. In the direct technique the antibacterial activity on all microorganisms were higher for MTA Fillapex sealer. In the indirect technique, both sealers exhibited similar antibacterial properties. Conclusion: The antibacterial effect of MTA Fillapex sealer was significantly more than that of AH 26 sealer in the direct technique. The antibacterial effects of both sealers were similar in the indirect technique. Keywords: Antibacterial; Enterococcus faecalis; Lactobacillus; MTA Fillapex; Sealers; Staphylococcus